Pertumbuhan Vegetatif dan Potensi Hasil Stek Ubi Jalar pada Varietas, Jenis Stek, dan Periode Simpan Stek yang Berbeda - Suwarto; Wahyuni, Ari; Bias Cintaning, Anis; Ayu Nabila, Diah; Neti, Natali; Rudang Astari Sinaga, Tamara (Politeknik Negeri Lampung, 2025)
Sweet potatoes are propagated using vegetative propagation, especially cuttings. The cuttings used can come from the shoots and stems. During the distribution to farmers, the cuttings undergo temporary storage that useful to help maintain moisture, temperature, and air circulation in an optimum state. The study aimed to determine the effect of variety, type of cuttings, length of storage, and their interaction on vegetative growth and potential cuttings produced by sweet potato plants. The study was arranged using a three-factor factorial Randomized Block Design with 4 replications. The first factor was sweet potato varieties composed of 2 levels, specifically Antin 3 (V1) and Beta 1 (V2). The second factor is the cuttings types composed of two levels, specifically shoots (S1) and stems (S2). The third factor is the storage period, which consists of 3 levels, specifically without storage (P0), 1 week of storage (P1), and 2 weeks of storage (P2). The observed variable consisted of cutting growth rate, primary branch length, secondary branch length, and number of branchs and cuttings potential. The results showed that the Beta 1 variety had better growth than the Antin 3 variety based on the criterion of shoot growth, secondary branch length, and cuttings potential. Beta 1 has a longer shelf life than Antin 3, which can be stored for 1 week. Cuttings planting material storage can reduce all observation criterion, specifically growth capacity, primary branch length, number of branchs, secondary branch length, and cuttings potential. Cuttings derived from the shoots produced better plant length than stem cuttings in the treatment without storage.